Ceilidhe every Saturday night - Gaelic League of London, GLL
Flyer advertising regular Ceilidhe every Saturday night at 74 Penton Street, London. Organised by Connradh na Gaedilge Lonndain = Gaelic League of London. A manuscript poem in Irish is on the reverse.